The Effect of Pharmacist Intervention on Knowledge, Attitudes, and Hemoglobin Levels Among Adolescent Girls in Preventing Anemia - Mirna Risna Lovinanda Lubis; Urip Harahap; Putri Chairani Eyanoer (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Anemia is a common health problem among adolescent girls and may negatively affect physical health, concentration, and future reproductive health. Aim: This study aimed to analyze the effect of pharmacist intervention on hemoglobin levels, knowledge, and attitudes of adolescent girls in preventing anemia in Ujung Batu District, North Padang Lawas Regency. Methods: A comparative experimental study with a one-group pretest-posttest design was conducted from October to November 2024. A total of 80 adolescent girls with anemia were selected using purposive sampling from junior high schools and Islamic boarding schools in Ujung Batu District. The intervention consisted of pharmacist-led education, counseling, and administration of iron supplementation tablets. Hemoglobin levels were measured using HemoCue Hb 301, while knowledge and attitudes were assessed using structured questionnaires. Data were analyzed using the Wilcoxon signed-rank test. Result: The results showed significant improvements after the intervention. Mean hemoglobin levels increased from 10.82 ± 0.49 g/dL to 13.35 ± 0.63 g/dL, knowledge scores increased from 44.75 ± 7.95 to 79.25 ± 7.50, and attitude scores increased from 67.23 ± 6.56 to 83.01 ± 5.12, with all variables showing statistical significance (p < 0.001). Conclusion: Pharmacist intervention was effective in improving hemoglobin levels, knowledge, and attitudes of adolescent girls regarding anemia prevention.